Knowledge of Primary Health Care Nurses on Sexuality in Climacteric (Research, Society and Development, 2022)
Objective: to analyze the knowledge of Primary Health Care nurses about women's sexuality in climacteric and their interfaces. Method: the present study is an integrative review. 873 publications were found in which the titles and abstracts were analyzed, as well as the proposed inclusion and exclusion criteria. Then, 171 publications were pre-selected to be read in full in order to critically analyze the results obtained. After the reading and analysis process, 39 publications were selected to compose the discussion and presentation of this integrative review. Results and discussion: in analysis, it was found that the literature brings the need for the nursing professional to work the theme of sexuality in a clear way, addressing the needs of the individual as a whole. Conclusion: in this way, the findings and reflections presented in this study can contribute to the improvement of care provided to climacteric women by nurses in the Family Health Strategy.